Differentiation of human foreskin fibroblast‐derived induced pluripotent stem cells into hepatocyte‐like cells. (29th August 2016) - Wang, Jianjun; Zhao, Ping; Wan, Zhihong; Jin, Xueyuan; Cheng, Yongqian; Yan, Tao; Qing, Song; Ding, Ning; Xin, Shaojie
Abstract : The aim of this study was to investigate the differentiation potential of induced pluripotent stem cells (iPSCs) derived from human foreskin fibroblasts (HFFs) into hepatocyte‐like cells (HLCs). The iPSCs were firstly induced by transduction of OCT4, SOX2, KLF4, and c‐MYC into HFFs using retrovirus. Afterwards, expressions of pluripotency factors were identified by semiquantitative reverse transcription–polymerase chain reaction and immunofluorescence staining, and karyotype, embryoid, and teratoma were observed by microscope. Then, iPSCs were gradually differentiated into endoderm cells, hepatic progenitor cells, and mature HLCs by special culture medium. During this process, differentiation efficiency into each kind of cells was evaluated by detecting SOX17, HNF4a, and ALB using flow cytometry, respectively. Besides, enzyme‐linked immunosorbent assay was conducted to detect the secretion of ALB in iPSC‐induced HLCs and quantitative reverse transcription–polymerase chain reaction was performed to detect the expression levels of hepatocyte‐specific genes. The iPSCs were successfully induced by HFFs, which exhibited typical embryonic stem cells morphology, positive alkaline phosphatase staining, normal diploid karyotype, and positive expression of various pluripotency factors. Meanwhile, spherical embryoid and teratoma with 3 germ layers were formed by iPSCs. The iPSCs were consecutively induced into endoderm cells, hepatic progenitor cells and mature HLCs, and the differentiation efficiency was 55.7 ± 2.9%, 45.7 ± 4.8%, and 35.0 ± 3.9%, respectively. Besides, the secretion of ALB and expression of various hepatocyte‐specific genes was highly detected in iPSC‐induced HLCs. The iPSCs were successfully derived from HFFs and then differentiated into HLCs, which proved a new source for hepatocyte transplantation. Highlights: HFFs were successfully induced into iPSCs by transduction of OCT4, SOX2, KLF4, and c‐MYC . Positive expressions of various pluripotency factors were exhibited in HFFs‐induced iPSCs. The iPSCs were consecutively induced into endoderm cells, hepatic progenitor cells, and mature HLCs. Various hepatocyte‐specific genes were highly expressed in iPSC‐induced HLCs.